SOCIALIZATION OF CORPORATE INCOME TAX ASPECTS FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN SOUTHEAST SULAWESI PROVINCE - Hadisantoso, Erwin; Wawo, Andi Basru; Dali, Nasrullah; Nurdin, Emillia; Anto, La Ode; Ramadhan, Andi Muh. Fuad; Triani, Neks; Syahrir, Sasmita Nabila; Chairunnas, Arnadi; Noki, Noki (International Journal of Engagement and Empowerment (IJE2), 2024)
This community service activity focuses on socializing Corporate Income Tax aspects for Micro, Small, and Medium Enterprises (MSMEs) in Southeast Sulawesi Province. The program aims to improve MSME owners' understanding and awareness of income tax obligations, contributing to increased state revenue. The counseling session uses an educational persuasive approach, including theoretical explanations and demonstrations. After this, discussions and Q&A sessions are held to ensure participants grasp the tax aspects of their businesses. This method is expected to help participants understand relevant taxation issues and provide practical knowledge on fulfilling tax obligations accurately and responsibly. Through this activity, MSME operators are encouraged to apply the taxation knowledge gained, enhancing tax compliance and their contribution to the national economy. This approach fosters awareness and supports the sustainable growth of MSMEs within the legal framework of taxation